Leiomiomas e leiomiosarcomas da região oral e maxilofacial: um estudo clinicopatológico e imunoistoquímico de uma série de casos - Gabriela Ribeiro de Araújo (2021)
Smooth muscle tumors are considered rare in the oral cavity, with the frequency of leiomyoma (LM) and leiomyosarcoma (LMS) being less than 1% of the total number of neoplasms diagnosed in this region. LM are clinically characterized as a slow and asymptomatic nodule, being classified as angioleiomyoma and solid LM. Histologically, solid LM appear as a proliferation of spindle cells with eosinophilic cytoplasm forming bundles or interlaced fascicles, while angioleiomyomas are composed of bundles of bland, well-differentiated smooth muscle cells and intervening variably sized blood vessels. Surgical removal is the recommended treatment and recurrences are extremely rare. LMS, on the other hand, presents clinically as a tumoral lesion that exhibits rapid and locally destructive growth, histologically showing a fascicular growth of spindle-shaped neoplastic cells, with figures of mitosis, cell atypia and tissue necrosis. The most used treatment is radical surgical excision, often showing local recurrences and distant metastases. Due to the long list of microscopic differential diagnoses of these two neoplasms, immunohistochemistry reactions are usually fundamental for the correct diagnosis. Thus, the aim of this study was to describe in detail the clinical, histopathological and immunohistochemical characteristics of a series of cases of LM and LMS affecting the oral and maxillofacial region. All cases diagnosed as LM and LMS in the period from 2000 to 2019, were recovered from the files of six oral diagnostic services. Clinical and demographic characteristics were obtained from patients' pathological records, while microscopic and immunohistochemistry characteristics were reviewed, by at least two authors simultaneously, and completed when necessary to confirm the diagnosis. Antibodies used in immunohistochemistry were: anti-α-SMA, muscle-specific actin(HHF-35), h- caldesmon and Ki67, however, whenever necessary, we used S100, desmin and CD34. Twenty-two LM and five LMS were obtained in the study. In the LM group, there was a predominance of males, with a mean age of 45.7 years. The upper lip was the most affected site, with 18 cases classified as angioleiomyoma and four as solid LM. The mean evolution time was 44.5 months and 91% of patients were asymptomatic. In the LMS group, there was a predominance of females, with a mean age of 47.6 years. The jaw was the most affected site. All patients were symptomatic, with pain, lower lip numbness and inferior alveolar nerve paresthesia, with evolution time ranging from 2- 4 months. Diffuse proliferation of spindle cells, with necrosis and mitotic figures, were frequent microscopic findings. LM and LMS were consistently positive for smooth α- SMA, HHF-35 and h-caldesmon. We concluded in this study that both LM and oral LMS are uncommon neoplasms, the latter usually presenting as a metastatic disease. H&E assessment can be very suggestive for oral LM, but immunohistochemical staining for h-caldesmon is strongly recommended to confirm the diagnosis of LMS.